Nutrient Distribution on the Plankton Community Structure in Bandengan and Panjang Island Water, Jepara - Niniek Widyorini; Ruswahyuni Ruswahyuni (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
The influence of freshwater tidals zone at Bandengan and Panjang Island could be seen by extensive finding of freshwater plankton such as Anabaena, Nitzschia, Oscillatoria, Tolypothrix, Surirella, Euglena, Volvox, and Spirogyra. Partially, salinity in Bandengan water was 30 – 33 o/oo, pH ranged between 8 – 9, and nitrite was zero, wich was in compliance with the criterian for seawater (Kep-02/MENKLH/I/88). The high level of SiO2 in Bandengan waters (1.20 – 3.29 mg/l) and Panjang Island (1.58 – 3.30 mg/l) supported the dominance of Chrysophyceae, especially Diatomae, in the study areas.  Keywords : Nutrient, Plankton, Bandengan, Panjang Island